Perancangan Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Dengan Metode Simple Additive Weighting (SAW) Berbasis Web - Akmaludin; Kussigit Santosa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the selection of outstanding students at SDIT Al-Iman only used academic scores as an assessment material so that the selection seemed subjective. While there are many other determining factors that can be considered in the selection of outstanding students. Elections based on this subjectivity have an impact on those who feel disadvantaged because the election is felt to be less transparent. Therefore, a decision support system is needed that can reduce subjectivity in selection of outstanding students so that it can assist schools in selection transparently. The Simple Additive Weighting (SAW) method is one of the decision-making methods which can add up the performance weights of each object that is different and has the same opportunity. In the decision-making process for selecting outstanding students at SDIT Al-Iman, criteria are needed to assist in making decisions, and each criterion has its own importance to determine the best alternative from the number of students in the class. With the making of this decision support system, it is hoped that it will be able to provide transparent assessments and be able to determine the best alternative choices to assist in the selection of outstanding students at SDIT Al-Iman.